Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Provided that $p\geq-1$, prove $(1+p)^n\geq1+np$ for all integers $n\geq 0$

Also, where in the calculation do I use $p\geq -1$?

Thanks guy!

share|cite|improve this question
up vote 1 down vote accepted

For base case, if $n = 0$, then $(1 + p)^0 = 1 \geq 1 $. So Equation trivially holds! No suppose it holds for $n$ in $Z^+$. Then $$ (1+p)^{n+1} = (1+p)^n(1+p) \geq (1+np)(1+p) = 1+np^2 + np + p \geq 1 +(n+1)p. $$ The proof is concluded by math induction.

share|cite|improve this answer
how did you come up with multiplying by 1+p on both sides? o-o its indeed a good trick – John Lee Oct 19 '12 at 4:37
Thats what You want to proof. The $n+1$ case! – ILoveMath Oct 19 '12 at 4:38
can i prove this without multiplying n+1 on both sides? and do i use this trick for all Induction problems? – John Lee Oct 19 '12 at 4:42
@LJym89 The term $n^2p$ should be $np^2$ (note that $n^2p$ could be negative). – Erick Wong Oct 19 '12 at 4:49

I think you use this : $(1+p)^n \geq 1 + np$ then $(1+p)^n(1+p) \geq (1+np)(1+p)$ if $p < -1$ then the inequality reversed, that is your question, right ?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.